The Impact of Employer Branding on Young Professionals: A Cross-Country Analysis - Pajunen, Julia (My University, 2023)
In today’s rapidly changing and ever globalising world, the need to attract and manage talent to and within organisations is crucial. The concept ‘war for talent’ was first introduced at the end of 20th century, and it has been one of the top challenges for companies ever since. As digitalisation has made it possible for information to spread rapidly, companies need to focus more carefully on their image both internally and externally from the organisation. In order to attract talent to an organisation the employer brand must reach and resonate in the potential employee. This study focuses on defining the attractiveness of an employer and determining the impact of employer branding from the employee perspective.

Tämän päivän yritysten haasteena on esiintyä houkuttavana työnantajana työntekijämarkkinoilla, jossa pula osaavasta työvoimasta mahdollistaa työntekijälle valinnan työnantajien välillä. Työnantajamielikuvamarkkinointi on yksi yritysten pääkeinoista vakuuttaa potentiaaliset osaajat työpaikan houkuttavuudesta, johon vaikuttavia tekijöitä ovat esimerkiksi työpaikkakulttuuri, rahallinen korvaus työpanoksesta sekä etenemismahdollisuudet uralla. Nuoret osaajat ovat potentiaalisia työntekijöitä yrityksille monella markkina-alueella, jonka vuoksi kilpailu osaajista ei ole ainoastaan paikallista vaan myös kansainvälistä. Tämän vuoksi yritysten tulee kehittää strategisia ratkaisuja työnantajamielikuvamarkkinoinnin saralla ollakseen houkuttava vaihtoehto työntekijöiden näkökulmasta. Uusien sukupolvien astuessa työmarkkinoille vaatimukset työnantajia kohtaan ovat muutoksessa, jonka vuoksi työnantajamarkkinoinnin tulee olla yritysten kehityksen keskiössä.
Keywords: recruitment of employees; branding; career development; employees; career planning; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business